2021
DOI: 10.2147/cmar.s295420
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prediction Model for Lateral Lymph Node Metastasis of Papillary Thyroid Carcinoma in Children and Adolescents

Abstract: Purpose Papillary thyroid carcinoma (PTC) in children and adolescents is prone to lateral lymph node metastasis (LNM), which is a high-risk factor for recurrence. However, few studies focused on identifying risk factors and establishing prediction models for lateral LNM of PTC in children and adolescents. Patients and Methods We retrospectively reviewed consecutive cases of children and adolescents with PTC undergoing thyroidectomy and cervical lymph node dissection bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
4
14
0
1
Order By: Relevance
“…However, due to the low incidence of PTC in children and adolescents and limited literature on the risk factors for LNM in this age group, it is necessary to do further study of the risk factors of LNM of PTC in children and adolescents. Our study found that maximal tumor size >2 cm and T stage were associated with central LNM (p < 0.05) and that maximal tumor size >2 cm, T stage, number of central LNM, and multifocality were the risk factors related to lateral LNM (p < 0.05), consistent with the report of the present study ( 18 , 19 ). Moreover, multivariate analysis results showed that the number of central LNM (OR 6.237 p = 0.005) was an independent risk factor for lateral LNM, in line with other research findings ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, due to the low incidence of PTC in children and adolescents and limited literature on the risk factors for LNM in this age group, it is necessary to do further study of the risk factors of LNM of PTC in children and adolescents. Our study found that maximal tumor size >2 cm and T stage were associated with central LNM (p < 0.05) and that maximal tumor size >2 cm, T stage, number of central LNM, and multifocality were the risk factors related to lateral LNM (p < 0.05), consistent with the report of the present study ( 18 , 19 ). Moreover, multivariate analysis results showed that the number of central LNM (OR 6.237 p = 0.005) was an independent risk factor for lateral LNM, in line with other research findings ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…The expert panel discussed the approach to a child with "incidental" DTC found on post-surgical pathology for another presumed benign thyroid condition, e.g., hemithyroidectomy for autonomous ETA Guidelines Pediatric Thyroid Nodules and DTC September 2022 | Version 8.2 Therefore, attempts have been made to generate risk factors and prediction models for lateral lymph node metastasis, as reported by Liang et al [94]. The authors assessed 102 children and adolescents with PTC and found that independent risk factors for lateral lymph node metastasis were multifocality, tumor size and the number of central lymph node metastases.…”
Section: Suggestion 9dmentioning
confidence: 99%
“…The incidence of positive lymph nodes can only be assessed in routine systematic neck dissection, which results in further patient qualification for radioiodine therapy. Therefore, attempts have been made to generate risk factors and prediction models for lateral lymph node metastasis, as reported by Liang et al ( 93 ). The authors assessed 102 children and adolescents with PTC and found that independent risk factors for lateral lymph node metastasis were multifocality, tumor size, and the number of central lymph node metastases.…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%
“…[82] показало, що у дітей з ПРЩЗ МФ, максимальний діаметр пухлини, ЕТП і метастази у ЦЛВ були незалежними чинниками ризику метастазування у ЛЛВ. У дослідженні W. Liang [67] виведено формулу розрахунку комбінованого предиктора для латерального метастазування у ЛВ при дитячому ПРЩЗ (Кількість метастазів + + 0,31• Розмір пухлини + 0,115 • Кількість метастазів у ЦЛВ), яка показала добру точність ( 2,2744). Прогностична цінність цих чинників для метастазування у ЛЛВ у порядку важливості така: комбінований предиктор, кількість метастатичних ЦЛВ, розмір пухлини та МФ.…”
Section: значення мультифокальностіunclassified